The role of knowledge management processes in enhancing the strategic agility of Iraqi insurance companies through the mediating part of strategic intelligence - KHADEM, ELHAM NEEMA; Mohammed, Mhsen Alwan; Mahmood, Yousif Riyadh (The journal of contemporary issues in business and government, 2021)
Knowledge management applies to a proper selection, analysis, and interpretation of data within and outside the company, based on the measurements and guidelines used to improve operations within the organization and enhance its productivity and improve its performance with its activities. The role of knowledge management processes as mediators to enhance Iraqi insurance companies’ strategic agility has been examined. Researchers have therefore been based on a questionnaire on a 5-scale basis. The questionnaire included two main sections: the first focused on research sample demographics and the second on study variables. The questionnaire was independent and distributed to a number of (150) people in Iraqi insurance companies. After the application process, researchers were able to get (125) properly completed questionnaires. This study has determined the normality of different variables. Since independent variables are not normally distributed, but error terms are normally distributed, this does not mean traditional linear regression disintegration. The data analysis results will also be valid. The results of this research have shown, according to the Equity Return, that the acquisition of expertise has a major effect on the organizational performance of Iraq. The study found that the business age moderates the link between information management and Iraqi insurance companies’ operating efficiency, measured by both assets and equity returns. Therefore, the research concluded that the company’s age moderates the relation between IM and corporate performance in Iraqi insurance companies. They are by the return on assets or equity income.